2010
DOI: 10.1007/s13181-009-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

“Pine Mouth” Syndrome: Cacogeusia Following Ingestion of Pine Nuts (Genus: Pinus). An Emerging Problem?

Abstract: We report a case of cacogeusia, specifically metallogeusia (a perceived metallic or bitter taste) following pine nut ingestion. A 36-year-old male presented with cacogeusia one day following ingestion of 10-15 roasted pine nuts (genus: Pinus). Symptoms became worst on postexposure day 2 and progressively improved without treatment over 5 days. There were no other symptoms and physical examination was unrevealing. All symptoms resolved without sequalae. We contemporaneously report a rise in pine nut-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 5 publications
(3 reference statements)
1
30
0
Order By: Relevance
“…The symptoms and incubation periods reported in the present trial are in close agreement with real case stories [1,5]. However, none of the volunteers experienced nausea, headache, diarrhoea or vomiting, nor did they experience symptoms lasting more than a week, as reported elsewhere [1,5].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The symptoms and incubation periods reported in the present trial are in close agreement with real case stories [1,5]. However, none of the volunteers experienced nausea, headache, diarrhoea or vomiting, nor did they experience symptoms lasting more than a week, as reported elsewhere [1,5].…”
Section: Resultssupporting
confidence: 90%
“…Despite the recent scientific focus, the causative agent responsible for PNS is not known, but the dysgeusia have so far been related to pine nuts from the species of P. armandii [2,4]. A few PNS cases have been reported [3,5], but to our knowledge, no controlled trials have yet been published. The aim of this small trial is to document the incubation periods, symptoms and their duration.…”
Section: Introductionmentioning
confidence: 99%
“…Pine nut syndrome is also known as pine mouth syndrome (PMS) or pine nut mouth syndrome [17,24,36,[43][44][45][46]. Kwegyir-Afful et al [47] introduced the term 'Pine Mouth Event'.…”
Section: Pine Nut Syndromementioning
confidence: 99%
“…Kwegyir-Afful et al [47] introduced the term 'Pine Mouth Event'. Medically, it is known as dysgeusia, metallogeusia or cacogeusia [10,43,46,48].…”
Section: Pine Nut Syndromementioning
confidence: 99%
“…In addition, occasional cases of diarrhea, headache and nausea have been reported to be associated with this syndrome [1]. Only a few studies of PNS have been reported [3–5], and one study has described the symptoms of pine nut-related dysgeusia in a total of six subjects [6]. A single species of pine nuts ( Pinus armandii ) has previously been associated with this syndrome [1,7,8], although recent studies have reported taste disturbances from samples containing nuts from a mixture of different Pinus species [2,9,10].…”
Section: Introductionmentioning
confidence: 99%